Validation measurements for the retrospective calculation of eye lens doses of interventional cardiologists. (September 2016) - Carinou, Eleftheria; Askounis, Panagiotis; Berus, Danielle; Ciraj-Bjelac, Olivera; Clairand, Isabelle; Covens, Peter; Dabin, Jérémie; Domienik, Joanna; Farah, Jad; Jurewicz, Joanna; Padovani, Renato; Struelens, Lara
Abstract : Introduction: The eye lens radiation-induced risk has been assessed for various population groups. In the framework of the European epidemiological study, EURALOC, an attempt is made to determine a possible dose-response relationship by targeting interventional cardiologists, a group of high exposure values. Purpose: In the study, eye lens doses are assessed using two approaches: combining self-reported data on working practices and eye lens doses from literature (approach 1); and converting the whole-body dose values to eye lens doses (approach 2). Eye lens dose measurements are performed to validate both approaches and to determine their associated uncertainties. Materials and methods: Eye lens dose measurements are performed on cardiologists in routine practice using commercially available dedicated eye lens dosemeters. Furthermore, whole-body dose values are obtained from whole-body dosemeters worn above the lead apron at the chest left position. Exposure information including tube orientation, operator position and orientation are collected. Results: The first values of eye lens doses measured in routine clinical conditions are in good agreement with eye lens dose estimates obtained with the two approaches No systematic errors have been found which is encouraging in order to continue using either of the two approaches for the estimation of eye lens doses and the final benchmarking against lens opacities. Conclusion: Preliminary measurements in clinical conditions validate the two suggested complementary dosimetric methodologies: the first, based on self-reported occupational history while the second, starts from personal whole body doses to determine the eye lens dose.